E-book Implementation: Lesson Learned from Nursing Students’ Learning Outcome - ผ่องอักษร ปานทิพย์; แจ่มจันทร์ ละเอียด (Nursing Journal of The Ministry of Public Health, 2018)
Higher education influence from advance technology, E-learning or blended learning is trendy advancement. E-book is well serviceable because of rapid access, up-to-date, comfortable, space free, portable, link to web or reference book promptly as well as no limit of place & time over the world. E-book for suctioning is develop and implement for nursing students. Lesson learned of the learning outcome from their reflective note reveal 1) The character of E-book; colorful teaching tool, descriptive, image and sound is persuade to reading as well as easier procedure. 2) Enhance knowledge and skill; usable for self tutorial, repeat at anytime, lesson exercise and easy to find the topic. 3) Improve confident; more confident than paper reading. Prepare before practice, portable for anytime review. 4) Pleasure; high satisfy, need more E-book for all nursing skills in order to review before practice or examination.